The greatest superpower : a novel - Sanchez, Alex, 1957- (Capstone Editions, a Capstone imprint, 2021)
Thirteen-year-old Jorge Fuerte struggles to deal his parents announcing thier divorce and with his father coming out as transgender, his twin brother's anger, and trying to keep the secret from his comic-loving friends and cool, confident, quirky new neighbor Zoey.